3D printing of thermoplastic polyurethane TPMS structures via selective laser sintering - Lee, Jia Shin (Nanyang Technological University, 2022)
According to American Society for Testing and Materials (ASTM), additive manufacturing (AM) is defined as “a process of joining materials to make objects from 3D model data, usually layer upon layer, as opposed to subtractive manufacturing methodologies”. This project aims to study the compressive behaviours and energy absorption potential of pure and blended triply periodic minimal surfaces (TPMS) lattice structures, printed through SLS using TPU as the main material. The compressive behaviours of each SLS printed TPU lattice structure during compressive test were observed, and the compression deformation stages were identified at a few stages of overall strain. It is observed in this study, for pure TPMS lattice structure, every single layer of lattice structure is compressed and deformed simultaneously throughout the compression process before densification. For blended TPMS lattice structure, the TPMS lattice structure with lower specific energy absorption will achieve complete compression deformation first and followed by the complete compression deformation of TPMS lattice structure with higher specific energy absorption. Pure TPMS lattice structure exhibits uniform compression deformation throughout compression process. The structure uniqueness in blended TPMS lattice structure, exhibits non-uniform compression deformation throughout compression process. Overall, Schwarz TPMS lattice structure is the best pure TPMS lattice structure with the highest energy absorption performance. Diamond-Schwarz TPMS lattice exhibited the highest energy absorption performance among blended TPMS lattice structures. The findings of higher onset densification strain and lightweight properties in Diamond-Schwarz TPMS lattice through this study, suggests that it has the potential to be used as an energy absorber in aerospace, automotive, and biomedical applications.